Clinicopathologic Features of Benign Neurogenic Tumor of Urinary Bladder. (May 2018) - Lee, Cheol; Kim, Bohyun; Song, Boram; Park, Jeong Hwan; Moon, Kyung Chul
Background . Benign neurogenic tumor involving the urinary bladder is a very rare and heterogeneous disease group. The clinical and radiological diagnosis may be difficult because of the disease's rarity and the histological similarities of each disease especially in needle biopsy specimens. However, accurate diagnosis is very important because the clinical course of each disease, even within the same diseases, is quite variable. In this study, we investigated 7 benign neurogenic tumors to better understand the rare disease entity in the urinary bladder by analyzing histological and immunohistochemical findings and comparing clinicopathologic features. Methods . We collected the cases by searching the medical records database of Seoul National University Hospital from 2000 to 2016. Results . We identified 3 ganglioneuromas, 2 schwannomas, 1 neurofibroma, and 1 granular cell tumor involving the urinary bladder. There were some limitations for the initial clinical and radiological diagnosis and even pathologic diagnosis using needle biopsy specimens. One infant patient was diagnosed radiologically with rhabdomyosarcoma, but the final diagnosis changed to ganglioneuromatosis. The initial needle biopsy diagnosis of 2 ganglioneuroma cases showed neurofibroma. All patients underwent a local resection, and 1 granular cell tumor patient suffered with pain because of a recurrent tumor. One neurofibromatosis patient had a lesion appear 34 months after the bladder operation, so he underwent repeated debulking operations, but he was diagnosed with malignant transformation after 8 years. Conclusions . An understanding of benign neurogenic tumors involving the urinary bladder and the sharing of rare experiences surrounding them are required to provide accurate diagnoses.